Ways We Respect Caribou: Teetł’it Gwich’in Rules - Wray, Kristine; Parlee, Brenda (ARCTIC, 2013)
Debates about respectful caribou harvesting have arisen during the most recent cycle of caribou population decline in the Western Arctic. One aspect of this debate has been focused on younger harvesters, who are perceived by some leaders, elders, and wildlife management officials as lacking in knowledge and skills for respectful harvesting compared to previous generations. Guided by previous research in northern Canada, we examined this issue through a collaborative study (2007 – 10) in the Teetł’it Gwich’in community of Fort McPherson. This paper uses the common pool resource concept of “rules” (verbalized by research participants as “ways we respect the caribou”) as the lens for exploring how knowledge about traditional practices of respectful harvesting varies with age. Rules for respectful harvesting were documented through semi-structured interviews with Teetł’it Gwich’in elders and used as a guide for assessing the knowledge of active harvesters ranging in age from 19 to 70. While the rules spoken by younger generations show some degree of simplification, there is generally a good match between the rules spoken by elders and those spoken by all generations of active harvesters. Although the depth of knowledge around each rule was not assessed, the results seem to illustrate continuity in key aspects of Teetł’it Gwich’in knowledge and skills for caribou harvesting. Further research is needed, however, into the mechanisms and processes of continuity, with particular attention to how traditional knowledge and skills are being adapted to meet the needs of current and future generations. Des débats entourant la récolte respectueuse du caribou ont surgi à la lumière du plus récent cycle de déclin de la population de caribous de l’Arctique de l’Ouest. Un des aspects de ces débats concerne les jeunes chasseurs qui, aux dires de certains chefs, aînés et représentants de la gestion de la faune, ne posséderaient pas les connaissances et les habiletés nécessaires à une récolte respectueuse et ce, comparativement aux ...